Prospect of Using Bacterial Bio-formulation to Suppress Bacterial Leaf Blight of Rice: A Case Study in Cianjur, West Java - Suryadi, Y.; Susilowati, D. N.; Priyatno, T. P.; Samudra, I. M.; Kadir, T. S.; Mubarik, N. R. (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is a major disease of rice in Indonesia which remains difficult to be controled. A number of bacterial isolates had been collected and screened for their ability to antagonize Xoo disease. Six isolates with the highest antagonistic potential and wide spectrum were chosen for studies based on their ability to control the disease. Bio-formulations consisted of single or mixtures (consortium) of the bacterial antagonists were formulated and tested for their effectiveness to control BLB under field trials in Cianjur, West Java. Efficacy of the bio-formulations against the disease on different rice cultivars varied significantly with HDB reductions ranging from 10.5% to 29.4% among the cultivars tested in the WS 2010/2011. The mixture of A6 + A8-bentonite showed a good ability to reduce BB infestation by up to 25%. Performance of the A6+A8-bentonite formulation also exceeded those of the individual isolate formulations, such as Burkholderia spp. E76-bentonite and S. marcescens SKM-kaolin. Application of the bacterial mixture formulation did not affect significantly on rice plant height, number of tillers, and weight of 1000 grains, but increased grain yield up to 8%. This study showed that the advantages of single or mixed cultures were apparent and further evaluation for application of bio-formulation need to be done under more intensive field conditions.